Iron monatomic nano-enzyme preparation loaded with sodium hydrosulfide as well as preparation method and application of iron monatomic nano-enzyme preparation

Through the iron single-atom nanoenzyme preparation loaded with sodium hydrosulfide, H2S gas is used to enhance the chemokinetics and photothermal therapy efficiency of single-atom nanoenzymes, the problems of H2O2 deficiency and heat shock protein interference are solved, and the tumor treatment effect is achieved remarkable Improve and protect health organizations.

CN119185539AActive Publication Date: 2024-12-27NANJING UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411379699.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-27
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

The therapeutic effect of existing single-atom nanoenzymes in tumor therapy is disturbed by the inadequate H2O2 and the upregulation of heat shock proteins (HSPs), making it difficult to enhance the efficiency of chemokinetic therapy (CDT) and photothermal therapy (PTT) simultaneously, and mild PTT pairs Healthy tissues have a higher risk of damage.

Method used

Using a iron single-atom nanoenzyme preparation loaded with sodium hydrosulfide, the porous iron single-atom nanoenzyme is used as a carrier, and sodium hydrosulfide is co-incubated with the nanoenzyme and enters its pores and coated with hyaluronic acid to form a nanoformula to enhance the Treatment effect.

Benefits of technology

The release of H2S gas inhibits catalase activity, increases OH generation, enhances CDT efficacy, and reduces ATP synthesis, inhibits HSPs expression, improves the mild PTT effect, significantly enhancing the sensitivity and therapeutic effect of tumor cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005069587250000011
    Figure HDA0005069587250000011
  • Figure HDA0005069587250000012
    Figure HDA0005069587250000012
  • Figure HDA0005069587250000013
    Figure HDA0005069587250000013
Patent Text Reader

Abstract

The invention provides a sodium hydrosulfide-loaded iron monatomic nano-enzyme preparation as well as a preparation method and application thereof, and the sodium hydrosulfide-loaded iron monatomic nano-enzyme preparation is constructed by taking iron monatomic nano-enzyme as a drug carrier to load sodium hydrosulfide and taking hyaluronic acid as an encapsulating agent and a targeting agent. On one hand, hydrogen sulfide gas released by sodium hydrosulfide can inhibit the activity of catalase in tumor cells, and the chemical kinetic treatment effect of the iron monatomic nano-enzyme is enhanced; on the other hand, mitochondrial dysfunction can be caused by increase of active oxygen, ATP synthesis is reduced, expression of heat shock protein is reduced, and mild photothermal therapy based on the iron monatomic nano-enzyme is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of nanomaterials, and in particular to a sodium hydrosulfide-loaded iron single-atom nanozyme preparation, a preparation method thereof, and an application thereof. Background Art

[0002] Single-atom nanozymes (SAzymes) have maximized atomic utilization, well-defined metal centers, and coordination environments, and have become the forefront of nanomedicine for tumor-specific treatment. There are two main induction pathways for cancer treatment based on SAzymes: one is the classic chemodynamic therapy (CDT) approach, which converts overexpressed H2O2 in tumors into highly toxic hydroxyl radicals (·OH) through the Fenton reaction, which can damage biomolecules such as DNA, proteins, and lipids, ultimately leading to cell death. In addition, due to the photothermal conversion properties of single-atom-anchored amorphous carbon carriers, photothermal therapy (PTT) based on SAzymes has become another way to eradicate tumors. However, its therapeutic effect is often interfered by insufficient H2O2 and upregulation of heat shock proteins (HSPs). At present, there are few methods to simultaneously enhance the CDT and PTT efficiencies of SAzymes to maximize the tumor treatment effect.

[0003] Hyperthermic PTT (>50°C) is a method that converts light energy into heat energy for tumor lesion ablation, with high spatiotemporal precision and less invasiveness. However, the heat diffusion generated by hyperthermic PTT inevitably causes inflammation and damage to adjacent healthy tissues. To address these issues, mild PTT (<45°C) is an alternative method that is more promising for safe cancer treatment, thereby avoiding damage to normal cells. Unfortunately, cellular thermotolerance is often caused by overexpression of HSPs. Current studies have found that H2S gas can downregulate the activity of mitochondrial respiration cytochrome c oxidase, thereby blocking the biosynthesis of adenosine triphosphate (ATP) energy to reduce HSPs expression and ultimately improve the efficacy of mild PTT. There are two main strategies to downregulate HSPs to increase the sensitivity of tumor cells to mild PTT: (1) inactivate or reduce existing HSPs; (2) reduce ATP energy supply to inhibit HSPs expression. Compared with the first strategy, ATP depletion cuts off the energy supply for protein biosynthesis, which would be a more attractive solution to bypass heat shock protein-mediated thermotolerance. Therefore, it is a challenging task to develop new green and efficient ways to reduce ATP production and fundamentally inhibit the expression of HSPs. Summary of the invention

[0004] In order to solve the above technical problems and maximize the synergistic therapeutic efficiency based on SAzymes, the present application provides an iron single-atom nanozyme preparation loaded with sodium hydrosulfide, wherein the nanopreparation uses a porous iron single-atom nanozyme as a carrier, and the sodium hydrosulfide enters the pores of the porous iron single-atom nanozyme after co-incubation with the porous iron single-atom nanozyme. Hyaluronic acid is used as an encapsulant and targeting agent to be coated on the surface of the iron single-atom nanozyme to assemble into a nanopreparation.

[0005] The present application also provides a method for preparing a sodium hydrosulfide-loaded iron single-atom nanozyme preparation, comprising the following steps:

[0006] Step 1: Preparation of porous iron single-atom nanozymes: Dissolve iron nitrate and zinc nitrate in a solvent to form solution 1, and dissolve 2-methylimidazole in a solvent to form solution 2. After mixing, stirring, aging, purifying and drying solution 1 and solution 2, Fe / Zn-ZIFs precursor powder is obtained. The Fe / Zn-ZIFs precursor powder is transferred to a porcelain boat and subjected to high-temperature pyrolysis in a tubular furnace to obtain a porous iron single-atom nanozyme.

[0007] Step 2: preparing an iron single-atom nanozyme loaded with sodium hydrosulfide: preparing an aqueous solution containing sodium hydrosulfide, dispersing the porous iron single-atom nanozyme prepared in step 1 into the aqueous solution containing sodium hydrosulfide, incubating overnight, and after the incubation is completed, centrifuging to obtain the iron single-atom nanozyme loaded with sodium hydrosulfide;

[0008] Step 3: Prepare a sodium hydrosulfide-loaded iron single-atom nanozyme preparation: disperse hyaluronic acid in water to obtain a solution containing hyaluronic acid, disperse the sodium hydrosulfide-loaded iron single-atom nanozyme obtained in step 2 in the aqueous solution containing hyaluronic acid and stir, and then centrifuge to obtain the sodium hydrosulfide-loaded iron single-atom nanozyme preparation.

[0009] The present application also provides the use of an iron single-atom nanozyme preparation loaded with sodium hydrosulfide in the preparation of anti-tumor drugs.

[0010] Beneficial Effects

[0011] Single-atom nanozymes are considered to be a promising nanomedicine for tumor treatment due to their excellent peroxidase activity, glutathione oxidase (GSHOx) activity, photothermal conversion performance and biocompatibility. The prepared Fe / SAzymes can convert the overexpressed H2O2 in the tumor into highly toxic ·OH through the Fenton reaction in the slightly acidic and H2O2-rich environment of the tumor, thereby destroying biological molecules such as DNA, proteins and lipids in the cell, and ultimately leading to cancer cell death. However, in actual situations, although H2O2 in the cell is overexpressed, it is still insufficient. Fe / SAzymes are loaded with sodium hydrosulfide and coated with hyaluronic acid to obtain nanoformulations. After being internalized by cells, the released H2S can inhibit the activity of catalase in cancer cells, thereby reducing the consumption of endogenous H2O2, and then increasing the amount of ·OH produced by single-atom nanozymes to enhance the CDT efficacy; experimental results show that the Fe / SAzymes@NaHS@HA treatment group exhibits stronger anti-tumor activity than the Fe / SAzymes@HA treatment group alone, which confirms that H2S can promote the CDT efficacy of Fe / SAzymes.

[0012] The synthesis of heat shock proteins is directly positively correlated with ATP content. ATP depletion cuts off the energy supply for protein biosynthesis, which will be a more attractive solution to circumvent heat shock protein-mediated thermotolerance. Since the carrier of the prepared Fe / SAzymes is an amorphous carbon structure, another important characteristic is that it has excellent photothermal conversion performance. The temperature change curves of different Fe / SAzymes concentrations under 1064nm laser irradiation can prove that it is an excellent photothermal conversion nanomaterial. The calculated photothermal conversion efficiency is 27.59%, which provides a photothermal ablation approach for cancer treatment. The above-mentioned H2S-assisted Fe / SAzymes produce excessive ·OH, which can not only enhance the CDT efficacy of Fe / SAzymes, but also excessive ·OH can cause mitochondrial dysfunction, resulting in a decrease in ATP production, and ultimately hindering the synthesis of heat shock proteins, thereby enhancing the mild PTT of Fe / SAzymes. Mild PTT synergizes with CDT to achieve significant tumor cell growth inhibition. In conclusion, the combined use of Fe / SAzymes and NaHS significantly enhanced the tumor therapeutic effect compared with the use of Fe / SAzymes alone, indicating that H2S can not only promote the CDT efficacy of Fe / SAzymes, but also promote the mild PTT of Fe / SAzymes, ultimately effectively improving the synergistic cancer therapeutic efficacy of Fe / SAzymes.

[0013] In the present embodiment, porous iron single-atom nanozymes are used as carriers. Sodium hydrosulfide enters the pores of porous iron single-atom nanozymes after co-incubation with them. Hyaluronic acid is used as an encapsulant and targeting agent to coat the surface of iron single-atom nanozymes to assemble into nanoformulations. The H2S released by NaHS enhances the tumor treatment effect of Fe / SAzymes. On the one hand, H2S enhances its CDT effect by inhibiting the activity of catalase. On the other hand, the ROS generated causes mitochondrial dysfunction, leading to a decrease in ATP synthesis and thus reducing the content of HSPs. Finally, under 1064nm laser irradiation, the mild PTT effect of Fe / SAzymes is enhanced. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 Transmission electron microscopy characterization of the morphology and structure of Fe / SAzymes in one embodiment of the present application is shown;

[0015] Figure 2 The high-angle annular dark-field scanning transmission electron microscopy characterization of Fe / SAzymes in one embodiment of the present application, iron (Fe), carbon (C), nitrogen (N) and the superposition analysis results of the three elements are shown;

[0016] Figure 3 High-angle annular dark field scanning transmission electron microscopy characterization of single-atom Fe in one embodiment of the present application is shown

[0017] Figure 4 The X-ray photoelectron spectroscopy test results of Fe / SAzymes in one embodiment of the present application are shown;

[0018] Figure 5 The nitrogen isothermal adsorption-desorption curve of the Fe / SAzymes mesoporous material in one embodiment of the present application is shown;

[0019] Figure 6 The peroxidase activity test results of Fe / SAzymes in one embodiment of the present application are shown;

[0020] Figure 7 The photothermal conversion performance test results of Fe / SAzymes in one embodiment of the present application are shown;

[0021] Figure 8 The zeta potential of Fe / SAzymes, Fe / SAzymes@NaHS and Fe / SAzymes@NaHS@HA in one embodiment of the present application is shown;

[0022] Fig. 9 The test results of Fe / SAzymes@NaHS@HA releasing H2S in one embodiment of the present application are shown;

[0023] Fig.10The cell viability diagram of PANC-1 cells after being treated with different drugs in one embodiment of the present application is shown. DETAILED DESCRIPTION

[0024] The preferred embodiments of the present invention will be described in detail below in conjunction with examples. It should be understood that the following examples are provided only for the purpose of illustration and are not intended to limit the scope of the present invention. Those skilled in the art may make various modifications and substitutions to the present invention without departing from the purpose and spirit of the present invention.

[0025] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0026] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0027] One embodiment of the present application provides a sodium sulfide-loaded iron single-atom nanozyme preparation, wherein the sodium sulfide-loaded iron single-atom nanozyme preparation uses a porous iron single-atom nanozyme as a carrier, and sodium sulfide enters the pores of the porous iron single-atom nanozyme after co-incubation with the porous iron single-atom nanozyme. Hyaluronic acid is used as an encapsulating agent and a targeting agent at the same time, and is coated on the surface of the iron single-atom nanozyme to assemble into a nano preparation. The transmission electron microscopy characterization of the morphology of the sodium sulfide-loaded iron single-atom nanozyme preparation Fe / SAzymes is as follows: Figure 1 shown.

[0028] One embodiment of the present application provides a method for preparing a sodium hydrosulfide-loaded iron single-atom nanozyme preparation, comprising the following steps:

[0029] Step 1: Preparation of porous iron single-atom nanozyme: dissolving iron nitrate and zinc nitrate in a solvent to form solution 1, dissolving 2-methylimidazole in a solvent to form solution 2, mixing, stirring, aging, purifying and drying solution 1 and solution 2 to obtain Fe / Zn-ZIFs precursor powder, transferring the Fe / Zn-ZIFs precursor powder to a porcelain boat, and obtaining porous iron single-atom nanozyme after high-temperature pyrolysis in a tubular furnace;

[0030] Step 2: preparing an iron single-atom nanozyme loaded with sodium hydrosulfide: preparing an aqueous solution containing sodium hydrosulfide, dispersing the porous iron single-atom nanozyme Fe / SAzymes prepared in step 1 into the aqueous solution containing sodium hydrosulfide, incubating overnight, and after the incubation is completed, centrifuging to obtain the iron single-atom nanozyme loaded with sodium hydrosulfide;

[0031] Step 3: Prepare a sodium hydrosulfide-loaded iron single-atom nanozyme preparation: disperse hyaluronic acid in water to obtain a solution containing hyaluronic acid, disperse the sodium hydrosulfide-loaded iron single-atom nanozyme obtained in step 2 in the aqueous solution containing hyaluronic acid and stir, and then centrifuge to obtain the sodium hydrosulfide-loaded iron single-atom nanozyme preparation.

[0032] In one embodiment, in step one, the final concentration of ferric nitrate is 0.30-0.50 mg / ml, the final concentration of zinc nitrate is 4.00-7.00 mg / ml, and the final concentration of 2-methylimidazole is 12.00-15.00 mg / ml; the solvent is methanol; the stirring time is 1 h, the aging time is 24 h, and the drying temperature is 60°C; the high-temperature pyrolysis condition is to increase the temperature to 800°C at 5°C / min in a nitrogen atmosphere, and maintain the target temperature for 2 h.

[0033] In one embodiment, the concentration of sodium hydrosulfide in step 2 is 16 mg / ml, and the concentration of iron single-atom nanozyme is 1 mg / ml; the incubation condition is 25°C; and the centrifugation condition is 16000 rpm, 8 min.

[0034] In one embodiment, the hyaluronic acid concentration in step three is 10 mg / ml; the stirring condition is 1 h at room temperature, and the centrifugation condition is 16000 rpm, 8 min.

[0035] One embodiment of the present application provides the use of the sodium hydrosulfide-loaded iron single-atom nanozyme preparation in the preparation of anti-tumor drugs.

[0036] In one embodiment, the concentration range of the nanoformulation is 0 μg / mL to 50 μg / mL.

[0037] In one embodiment, the nanoformulation is irradiated using a 1064 nm near-infrared laser.

[0038] Preparation of nanocarriers:

[0039] 1. Preparation of porous iron single-atom nanozymes (Fe / SAzymes)

[0040] First, 0.08g Fe(NO3)3·9H2O and 1.116g Zn(NO3)2·6H2O were dissolved in 100mL methanol to form solution 1. 2.608g 2-methylimidazole was dissolved in 100mL methanol to form solution 2. Solution 1 was poured into solution 2 at room temperature and stirred vigorously for 1h. Then the mixed solution was aged for 24h, and finally the yellow precipitate was purified with methanol 5 times, and then dried at 60℃ to obtain the precursor Fe-Zn ZIFs. Finally, the synthesized Fe-Zn ZIFs precursor was placed in a porcelain boat, and the temperature was raised to 800℃ at 5℃ / min in a N2 atmosphere, and then kept at this temperature for 2h to obtain Fe / SAzymes.

[0041] 2. Preparation of iron single-atom nanozymes loaded with sodium hydrosulfide (Fe / SAzymes@NaHS)

[0042] 1 mg of Fe / SAzymes obtained in step 1 was weighed into 1 mL of PBS (pH=7.4) and ultrasonically mixed, and then 16 mg of NaHS was weighed into the above solution and incubated overnight. After the incubation, centrifugation (16000 rpm, 8 min) was performed to obtain Fe / SAzymes@NaHS.

[0043] 3. Preparation of iron single-atom nanozyme preparation loaded with sodium hydrosulfide (Fe / SAzymes@NaHS@HA)

[0044] Weigh 5 mg of hyaluronic acid (HA) into 500 μL of 1 mg / mL Fe / SAzymes@NaHS (step 2) solution, and stir slowly with a magnetic bar for 1 h to coat HA on the surface of the nanozyme. After stirring, centrifuge to obtain the sodium hydrosulfide-loaded iron single-atom nanozyme preparation.

[0045] Characterization of Nanocarriers:

[0046] 1. Synthesis and characterization of Fe / SAzymes

[0047] like Figure 1 As shown in Figure 2, transmission electron microscopy (TEM) images show that FeSAzymes have good geometric morphology and an average diameter of about 120 nm. In order to confirm whether Fe exists in the Fe / SAzymes structure, elemental analysis was performed. Figure 2 The results showed that Fe, C and N elements existed in FeSAzymes. Figure 3As shown in Figure 2, the high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) image confirmed the presence of monodisperse iron atoms, and thus the Fe / SAzymes were successfully synthesized. Secondly, by X-ray photoelectron spectroscopy (XPS), the N1s spectrum in Fe / SAzymes showed three peaks at 398.4 eV (pyridine N), 400.5 eV (pyrrole N) and 402.2 eV (graphite N) ( Figure 4 ). Among them, pyridinic N helps to stabilize the monodisperse Fe atoms, thus facilitating the catalytic activity of Fe / SAzymes. Figure 5 As shown in A, Fe / SAzymes were tested by N2 adsorption / desorption experiments. Figure 5 Figure B shows that the average pore size is 1.39 nm, confirming the existence of its porous structure.

[0048] 2. Test of peroxidase (POD) activity and photothermal conversion performance of Fe / SAzymes

[0049] The typical colorimetric reaction of 3,3',5,5'-tetramethylbenzidine (TMB) with ·OH verified the POD activity of Fe / SAzymes, which catalyzed TMB to generate blue oxidized TMB (oxTMB) and produced a distinct UV-visible characteristic absorption peak at 652 nm. Different combinations of TMB analysis were explored, such as Figure 6 As shown in Figure A, Fe / SAzymes have significantly enhanced POD catalytic activity compared to CN. Figure 6 Figure B shows that Fe / SAzymes has acid-dependent POD activity at different pH values ​​(5.0, 6.0 and 7.4), which indicates that Fe / SAzymes tend to convert H2O2 into abundant ·OH in a slightly acidic environment. The temperature rise curves of Fe / SAzymes solutions at different concentrations prove that Fe / SAzymes can be used as an excellent photothermal conversion nanomaterial ( Figure 7 ), and the photothermal conversion efficiency was calculated to be 27.59%.

[0050] 3. Characterization test of Fe / SAzymes@NaHS@HA and H2S release performance test.

[0051] like Figure 8As shown, the Zeta potential of Fe / SAzymes is -11.43mV. After NaHS enters the interior of Fe / SAzymes, the Zeta potential of Fe / SAzymes@NaHS is -15.80mV, which indicates that the loading of NaHS is successful. In order to prevent the leakage of NaHS, a layer of hyaluronic acid (HA) is wrapped on the surface of Fe / SAzymes, and the Zeta potential changes from the original -15.80mV to -17.52mV, which indicates that the assembly of Fe / SAzymes@NaHS@HA nanoformulation is successful. Next, the H2S detection kit is used, that is, H2S reacts with N,N-dimethyl-p-phenylenediamine and ammonium ferric sulfate to generate methylene blue. Methylene blue has a maximum absorption peak at around 665nm, as shown in Fig. 9 As shown, Fe / SAzymes@NaHS@HA has an obvious characteristic absorption peak after being treated with the kit, proving that it can release H2S gas.

[0052] Application of Nanocarriers:

[0053] The cytotoxicity was detected using a standard cell counting kit-8 (CCK-8). PANC-1 cells were cultured in 96-well plates at a cell density of 1×10 4 / well (100μL RPMI-1640 medium) and cultured for 12h until the cells adhered. Next, the cells were incubated with (1) PBS; (2) Fe / SAzymes@HA; (3) Fe / SAzymes@HA+laser; (4) Fe / SAzymes@NaHS@HA; (5) Fe / SAzymes@NaHS@HA+laser. After incubating the cells with drugs for 12h, the cells were illuminated with a 1064nm laser (0.58W cm -2 , 6min) irradiated PANC-1 cells. The infrared camera monitored the highest temperature during the irradiation period to be below 45°C. After incubation for 24h, the culture medium was aspirated, and the cells were cultured with fresh culture medium containing 10μL CCK-8 for 1h. Finally, the cell viability was evaluated by detecting the absorbance of CCK-8 at 450nm.

[0054] like Fig.10 As shown in Figure A, the antitumor activity of Fe / SAzymes against PANC-1 cells increased with the increase of Fe / SAzymes concentration from 0 to 140 μg / mL, which was attributed to the slightly acidic pH and abundant endogenous H2O2 in the tumor microenvironment. Then, Fe / SAzymes@NaHS@HA was used to study the synergistic therapeutic effect between H2S gas and single-atom nanozymes. The results showed that Fe / SAzymes@NaHS@HA treatment exhibited stronger antitumor activity than Fe / SAzymes@HA treatment alone, which confirmed that H2S can promote the CDT efficacy of Fe / SAzymes ( Fig.10 (B). In addition, under 1064nm laser irradiation, the cell viability after Fe / SAzymes@HA treatment was less than 65%, while the cell viability after Fe / SAzymes@NaHS@HA treatment dropped to less than 40%. Compared with the use of Fe / SAzymes alone, the combination of Fe / SAzymes and NaHS significantly enhanced its mild PTT (<45℃) effect, indicating that H2S can not only promote the CDT efficacy of Fe / SAzymes, but also promote its mild PTT, ultimately effectively improving the synergistic cancer treatment efficacy of Fe / SAzymes.

[0055] The present application example uses porous iron single-atom nanozymes as carriers, sodium hydrosulfide enters the structure after co-incubation with porous iron single-atom nanozymes, and hyaluronic acid is used as an encapsulating agent and a targeting agent to be coated on the surface of the iron single-atom nanozymes to assemble into a nanoagent. The H2S released by NaHS enhances the tumor treatment effect of Fe / SAzymes. On the one hand, H2S enhances its CDT effect by inhibiting the activity of catalase. On the other hand, the ROS generated causes mitochondrial dysfunction, leading to a decrease in ATP synthesis and thus reducing the content of HSPs. Finally, under 1064nm laser irradiation, the mild PTT effect of Fe / SAzymes is enhanced. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A sodium hydrosulfide-loaded iron single-atom nanozyme preparation, characterized in that: The sodium hydrosulfide-loaded iron single-atom nanozyme preparation uses porous iron single-atom nanozyme as a carrier. Sodium hydrosulfide enters the pores of the porous iron single-atom nanozyme after co-incubation with the porous iron single-atom nanozyme. Hyaluronic acid is used as an encapsulating agent and a targeting agent at the same time and is coated on the surface of the iron single-atom nanozyme to assemble into a nanopreparation.

2. The method for preparing the sodium hydrosulfide-loaded iron single-atom nanozyme preparation according to claim 1, characterized in that: The following steps are involved: Step 1: Preparation of porous iron single-atom nanozyme: dissolving iron nitrate and zinc nitrate in a solvent to form solution 1, dissolving 2-methylimidazole in a solvent to form solution 2, mixing, stirring, aging, purifying and drying solution 1 and solution 2 to obtain Fe / Zn-ZIFs precursor powder, transferring the Fe / Zn-ZIFs precursor powder to a porcelain boat, and obtaining porous iron single-atom nanozyme after high-temperature pyrolysis in a tubular furnace; Step 2: preparing an iron single-atom nanozyme loaded with sodium hydrosulfide: preparing an aqueous solution containing sodium hydrosulfide, dispersing the porous iron single-atom nanozyme prepared in step 1 into the aqueous solution containing sodium hydrosulfide, incubating overnight, and after the incubation is completed, centrifuging to obtain the iron single-atom nanozyme loaded with sodium hydrosulfide; Step 3: Prepare a sodium hydrosulfide-loaded iron single-atom nanozyme preparation: disperse hyaluronic acid in water to obtain a solution containing hyaluronic acid, disperse the sodium hydrosulfide-loaded iron single-atom nanozyme obtained in step 2 in the aqueous solution containing hyaluronic acid and stir, and then centrifuge to obtain the sodium hydrosulfide-loaded iron single-atom nanozyme preparation.

3. The method for preparing the sodium hydrosulfide-loaded iron single-atom nanozyme preparation according to claim 2, characterized in that: In step 1, the final concentration of ferric nitrate is 0.30-0.50 mg / ml, the final concentration of zinc nitrate is 4.00-7.00 mg / ml, and the final concentration of 2-methylimidazole is 12.00-15.00 mg / ml; the solvent is methanol; the stirring time is 1 hour, the aging time is 24 hours, and the drying temperature is 60°C; the high-temperature pyrolysis conditions are to increase the temperature to 800°C at 5°C / min in a nitrogen atmosphere, and maintain the target temperature for 2 hours.

4. The method for preparing the sodium hydrosulfide-loaded iron single-atom nanozyme preparation according to claim 2, characterized in that: In step 2, the concentration of the aqueous solution containing sodium hydrosulfide is 16 mg / ml, and the concentration of the iron single-atom nanozyme is 1 mg / ml; the incubation condition is 25°C; and the centrifugation condition is 16000 rpm, 8 min.

5. The method for preparing the sodium hydrosulfide-loaded iron single-atom nanozyme preparation according to claim 2, characterized in that: In step 3, the concentration of the solution containing hyaluronic acid is 10 mg / ml; the stirring condition is 1 h at 25° C., and the centrifugation condition is 16000 rpm for 8 min.

6. Use of the sodium hydrosulfide-loaded iron single-atom nanozyme preparation according to claim 1 in the preparation of anti-tumor drugs.

7. The use according to claim 6, characterized in that: The concentration range of the sodium hydrosulfide-loaded iron single-atom nanozyme preparation is 0 μg / mL to 50 μg / mL.

8. The use according to claim 7, characterized in that , the iron single-atom nanozyme preparation loaded with sodium hydrosulfide was irradiated using a 1064nm near-infrared laser.

Citation Information

Patent Citations

  • Application of Fe-N-C monatomic nano-enzyme

    CN113181358A

  • Monatomic nano-enzyme as well as preparation method and application thereof

    CN114011422A

  • Preparation method of iron monatomic nano-enzyme for specific treatment of tumors

    CN117298150A

  • Novel GDY-loaded CuBi bimetallic nano-catalyst with nano-enzyme activity for tumor treatment and preparation method of novel GDY-loaded CuBi bimetallic nano-catalyst

    CN118403173A

  • Nanoparticle capable of releasing carbon monoxide in a responsive manner, preparation method therefor and use thereof

    WO2023202092A1